Methyl donor supplementation blocks the adverse effects of maternal high fat diet on offspring physiology. - Jesselea Carlin (PLoS ONE, 2013)
Maternal consumption of a high fat diet during pregnancy increases the offspring risk for obesity. Using a mouse model, we have previously shown that maternal consumption of a high fat (60%) diet leads to global and gene specific decreases in DNA methylation in the brain of the offspring. The present experiments were designed to attempt to reverse this DNA hypomethylation through supplementation of the maternal diet with methyl donors, and to determine whether methyl donor supplementation could block or attenuate phenotypes associated with maternal consumption of a HF diet. Metabolic and behavioral (fat preference) outcomes were assessed in male and female adult offspring. Expression of the mu-opioid receptor and dopamine transporter mRNA, as well as global DNA methylation were measured in the brain. Supplementation of the maternal diet with methyl donors attenuated the development of some of the adverse effects seen in offspring from dams fed a high fat diet; including weight gain, increased fat preference (males), changes in CNS gene expression and global hypomethylation in the prefrontal cortex. Notable sex differences were observed. These findings identify the importance of balanced methylation status during pregnancy, particularly in the context of a maternal high fat diet, for optimal offspring outcome.